Analisis Manajemen Penghimpunan Zakat (FUNDING) Pada Badan Amil Zakat Nasional Kabupaten Langkat - Zidane Theo Mirantha; Rahnan Fatari; Muhammad Nur Iqbal (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to analyze the strategies for zakat collection, distribution, and utilization, as well as transparency and accountability in zakat management at the National Zakat Agency (BAZNAS) in Langkat. The study employed a qualitative method with a descriptive approach. Data were obtained through direct interviews with BAZNAS officials in Langkat and supported by relevant documentation. The research focused on zakat collection strategies to attract recipients (muzakki), patterns of zakat distribution and utilization to improve the welfare of those who mustahik (receiver), and the application of transparency and accountability principles in zakat fund management. The results indicate that BAZNAS Langkat implements various zakat collection strategies through outreach, collaboration with government and private institutions, the establishment of Zakat Collection Units (UPZ), and the use of digital technology through e-zakat services. In distributing and utilizing zakat, BAZNAS not only distributes consumer assistance but also implements productive zakat programs in the form of business capital assistance, skills training, and business mentoring to increase the economic independence of those who mustahik (receiver). Meanwhile, transparency and accountability are realized through the preparation of financial reports in accordance with sharia accounting standards, the implementation of internal and external audits, and the dissemination of information on zakat fund management to the public. Although several obstacles remain, such as low awareness among some communities about distributing zakat through official institutions and limited funds to meet the needs of those entitled to receive it, overall zakat management at the Langkat BAZNAS has been running well and contributing to improving community welfare.